Shop manual for advanced engine performance - Schnubel, Mark (Today's Technician, 2006)
Covers the advanced topics of drivability, emissions testing, and engine diagnostics in depth. This new book features a thorough study of On-Board-Diagnostic generation II (OBD II) Continuous Monitors and Non-Continuous Monitors strategies, a chapter on Emission Control and Evaporative Systems, OBD II generic Diagnostic Trouble Codes identification and diagnosis, and Malfunction Indicator Light Strategies. Advanced use of On-Board Diagnostic Scanners and Digital Storage Oscilloscopes is also discussed.